2019
DOI: 10.1093/jncics/pkz037
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Important Differences for Interpreting EORTC QLQ-C30 Scores in Patients With Advanced Breast Cancer

Abstract: Background We aimed to estimate the minimally important difference (MID) for interpreting group-level change over time, both within a group and between groups, for the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire core 30 (EORTC QLQ-C30) scores in patients with advanced breast cancer. Methods Data were derived from two published EORTC trials. Clinical anchors (eg, performance status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 20 publications
6
74
2
Order By: Relevance
“…A similar MID range has been previously reported in patients with breast cancer [8,20], small-cell lung cancer [8], brain cancer [14] and lung cancer [13] and in pooled data across multiple cancer sites [9,10]. Also in line with previous findings [12,13,14,20], it is important to note that our MIDs varied according to the EORTC QLQ-C30 scale and direction of change (improvement versus deterioration). Furthermore, as highlighted by Cocks et al [9,10], the 5-10 point threshold is not always achievable in all settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar MID range has been previously reported in patients with breast cancer [8,20], small-cell lung cancer [8], brain cancer [14] and lung cancer [13] and in pooled data across multiple cancer sites [9,10]. Also in line with previous findings [12,13,14,20], it is important to note that our MIDs varied according to the EORTC QLQ-C30 scale and direction of change (improvement versus deterioration). Furthermore, as highlighted by Cocks et al [9,10], the 5-10 point threshold is not always achievable in all settings.…”
Section: Discussionsupporting
confidence: 88%
“…Based on their overlapping results, mean differences ≥ 10 points have been commonly considered as clinically meaningful when interpreting EORTC QLQ‐C30 scale scores [19]. Nevertheless, there is increasing empirical evidence that MIDs can depend on the HRQOL scale, direction of change scores (improvement versus deterioration) and disease setting [9,10,12–14,20], implying that a global rule for MIDs applicable to all contexts is highly unlikely [21]. Therefore, there is a need to gather more empirical evidence on MID patterns across scales of the EORTC QLQ‐C30 and across disease sites [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that some of the differences in mean scores were small when taken in context of the 0-100 scale, so may be of little clinical or practical importance. For example, for EORTC QLQ-C30 global health status, it has been suggested that a difference of 8 points or more is important 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The choice of a clinically relevant difference, i.e., ≥10 points on a scale, may also have impacted our results. Although this value is universally accepted as a clinically meaningful change and used in cancer clinical trials, recent research has shown that this value may be different for different cancers and may not be applicable to changes on the individual patient level [ 25 , 26 , 27 ]. More appropriately defined clinically relevant differences may therefore be useful in both clinical trials and practice, when evaluating the impact of treatment over time.…”
Section: Discussionmentioning
confidence: 99%